2012
DOI: 10.1080/00222895.2012.746281
|View full text |Cite
|
Sign up to set email alerts
|

Interactions Between Tactile and Proprioceptive Representations in Haptics

Abstract: Neuroprosthetic limbs, regardless of their sophisticated motor control, require sensory feedback to viably interact with the environment. Toward that aim, the authors examined interrelationships between tactile and proprioceptive sensations. Through human psychophysics experiments, they evaluated error patterns of subjects estimating hand location in a horizontal 2-dimensional workspace under 3 tactile conditions. While tactile cues did not significantly affect the structure of the pattern of errors, touching … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 54 publications
1
7
0
Order By: Relevance
“…Conversely, a finger-position matching task has been reported to be affected by nerve block and cutaneous anesthesia [ 9 ], indicating that cutaneous afferents may provide a crude position sense for the fingers. Moreover, it has been shown that the localization of a proprioceptive target (i.e., the fingertip) was improved when participants contacted a surface with their target fingertip, which provides them with tactile feedback [ 10 12 ]. Similarly, accuracy in pointing movements was enhanced when endpoint contact occurred with the effector fingertip [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, a finger-position matching task has been reported to be affected by nerve block and cutaneous anesthesia [ 9 ], indicating that cutaneous afferents may provide a crude position sense for the fingers. Moreover, it has been shown that the localization of a proprioceptive target (i.e., the fingertip) was improved when participants contacted a surface with their target fingertip, which provides them with tactile feedback [ 10 12 ]. Similarly, accuracy in pointing movements was enhanced when endpoint contact occurred with the effector fingertip [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, digital anesthesia resulted in impaired fingertip localization [ 11 ] as well as decreased movement accuracy during typing [ 14 ]. This relationship between touch and proprioception is likely to be explained by the convergence of proprioceptive and tactile signals at the cortical level; electrophysiological recordings in monkey have shown that neurons in the hand representation of the primary somatosensory cortex code both tactile and proprioceptive modalities during a reach-to-grasp task [ 12 , 15 ]. It has also been established that neurons in the somatosensory cortex have both cutaneous and proprioceptive receptive fields [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…This may be because the feel of the drill‐based manipulandum is more familiar. There is also evidence that the tactile and proprioceptive systems may provide complementary information so it is possible that drill vibration may improve participants' ability to navigate within the 3D operative field …”
Section: Discussionmentioning
confidence: 99%
“…Prior work suggests that tactile and proprioceptive inputs are encoded simultaneously in unimpaired individuals (Rincon-Gonzalez et al, 2012 ). For instance, non-weight bearing contact of the fingertip against a surface can improve the accuracy of perceived posture.…”
Section: Introductionmentioning
confidence: 99%
“…Intracortical microstimulation has been used in brain–machine interfaces for the provision of tactile and proprioceptive feedback (Velliste et al, 2008 ; Rincon-Gonzalez et al, 2012 ). In non-human primate studies, electrical stimulation in somatosensory cortex has been used to convey limb movement, although the provision of absolute limb position remains a challenge, irrespective of the neural interface method being used (London et al, 2008 ).…”
Section: Introductionmentioning
confidence: 99%